Dinamika Kedekatan Emosional Anggota IKAMASI Yogyakarta dalam Perspektif Interaksi Simbolik - Tarri Afrianingsih; Olla Agustia Leriani; Alfian Muhazir (CV. ITTC INDONESIA, 2026)
This study examines the dynamics of emotional closeness in cross-gender friendships among members of IKAMASI Yogyakarta (Ikatan Keluarga Mahasiswa Bekasi Yogyakarta), a regional student organization. A qualitative descriptive-interpretive approach was used with data collected through in-depth interviews with seven informants: the chairman, male members, and female members. The theoretical framework integrates Weick's organizational communication theory (enactment, selection, retention), Blumer's symbolic interactionism (meaning, language, thought), and Rubin's gender theory. Findings show that emotional closeness develops gradually through layered organizational activities — from formal events such as Makrab and Malak to informal gatherings at coffee shops and dormitories. Members actively filter communication to manage emotional ambiguity in cross-gender interactions, while collective memory transmitted through shared stories shapes interaction norms across generations. Four informal ambiguity-management strategies were identified: direct family-style communication, contextual selectivity, self-restraint based on collective memory, and separation of personal matters from organizational affairs. These findings contribute a new dimension to the study of organizational communication and symbolic interaction within Indonesian regional student communities.